Penguatan Karakter Siswa melalui Seminar Pendidikan di SDN Mekarsari - Rahmadani, Kurniati; Fatoni, Ana Utami; Pardiman, Pardiman; Apriansyah, Rizki; Pasaribu, Sartika; Lisana, Rotudiah Hayu; Putri, Febrianti Dwi; Falatul Bukhori, Ido Atu (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The educational seminar conducted by KKM Group 57 at SDN 1 Mekarsari, Rangkasbitung District, was part of a community service program aimed at improving students' understanding of the importance of active, creative, and disciplined learning. This activity was motivated by low student learning motivation, both intrinsic and extrinsic. Students tended to be less enthusiastic, rarely asked questions, and were inactive in classroom learning activities. This seminar was designed as an educational effort to introduce effective and enjoyable learning strategies. The implementation method included interactive material delivery, a question-and-answer session, and the distribution of worksheets to encourage active participation. The activity was carried out face-to-face with the support of a teacher as an additional facilitator. The implementation results showed an increase in student enthusiasm and courage in expressing opinions, as well as a growing interest in a more dynamic learning process. Teachers also gained new insights to develop more engaging learning methods. This activity is expected to become a model of community service that can be replicated in elementary schools in rural areas, to strengthen the synergy between students, educators, and the community in improving the quality of basic education.